Ceding and Succeeding: How the Altruistic Can Benefit from the Selfish in Joint Decisions. Issue 4 (9th April 2019) - Lowe, Michael; Nikolova, Hristina; Miller, Chadwick J.; Dommer, Sara Loughran
Abstract : We examine how the interplay of two partners' interpersonal orientations (selfish vs. altruistic) in a decision‐making dyad impacts the extent to which the joint decision matches each partners' individual a priori preferences. Two experiments, in which we manipulate and measure interpersonal orientations, as well as examine real consumption decisions, demonstrate the benefit of mismatching interpersonal orientations (selfish‐altruistic) in dyadic decisions. Specifically, altruistic and selfish consumers reach joint decisions that better reflect their individual preferences when working with a partner who has the opposite interpersonal orientation (heterogeneous dyad) versus a matching one (homogeneous dyad). Initial evidence suggests that this effect occurs because homogeneous dyads are more prone to engage in negotiation (communication that involves departure from one's initial position to a mutually serving position) than heterogeneous dyads. This leads homogeneous dyads to focus more on equally preferred options than on their own most preferred options, which pushes them further down both partners' preferences lists. This research contributes to the literature on joint decision making and has important implications for consumer well‐being.